L'île d'Anjouan figure de la balkanisation de l'archipel des Comores - François Taglioni (EchoGéo)
Union of the Comoros is experiencing chronic political instability since its independence in 1975. From coups attempts to coup, from constitutional developments to national reconciliation, the Union is fragile and tries to resist with an endemic balkanization. It is embodied with the political affiliation of the fourth island of the Comoros archipelago, Mayotte, in the French Republic and with the separatist attempts of Anjouan and Moheli. In this tense political context occurred on March 25, 2008 the landing in Anjouan of an international force under the aegis of the African Union to overthrow President Mohamed Bacar. Union of the Comoros illustrates the obstacles of a national cohesion within a multi-insular state wrestling with heavy political difficulties and persistent economic and human development problems.